Sufficient conditions for oscillations of all solutions of a class of impulsive differential equations with deviating argument. (1996) - Bainov, D. D.; Dimitrova, M. B.
Abstract : Sufficient conditions are found for oscillation of all solutions of impulsive differential equation with deviating argument.